Acute and Delayed Neuromuscular Alterations Induced by Downhill Running in Trained Trail Runners: Beneficial Effects of High-Pressure Compression Garments - Ehrström, Sabine; Gruet, Mathieu; Giandolini, Marlene; Chapuis, Serge; Morin, Jean-Benoit; Vercruyssen, Fabrice (Frontiers in Physiology, 2018)
Introduction: The aim of this study was to examine, from a crossover experimental design, whether wearing high-pressure compression garments (CGs) during downhill treadmill running affects soft-tissue vibrations, acute and delayed responses in running economy (RE), neuromuscular function, countermovement jump and perceived muscle soreness. Methods: Thirteen male trail runners habituated to regular eccentric training performed two separate 40-min downhill running (DHR, –8.5°) sessions while wearing either CGs (15-20 mmHg for quadriceps and calves) or control garments (CON) at a velocity associated with 55% of VO2max, with a set of measurements before (Pre-), after (Post-DHR) and one day after (Post-1D). No CGs was used within the recovery phase. Perceived muscle soreness, countermovement jump and neuromuscular function (central and peripheral components) of knee extensors (KE) and plantar flexors (PF) were assessed. Cardiorespiratory responses (e.g. heart rate, ventilation) and RE, as well as soft-tissue vibrations (root mean square of the resultant acceleration, RMS Ar) for vastus lateralis and gastrocnemius medialis were evaluated during DHR and in Post-1D. Results: During DHR, mean values in RMS Ar significantly increased over time for the vastus lateralis only for the the CON condition (+11.6%). RE and cardiorespiratory responses significantly increased (i.e. alteration) over time in both conditions. Post, small to very large central and peripheral alterations were found for KE and PF in both conditions. However, the deficit in voluntary activation was significantly lower for KE following CGs (–2.4%), compared to CON (–7.9%) conditions. No significant differences in perceived muscle soreness and countermovement jump were observed between conditions whatever the time period. Additionally, in Post-1D, the CGs condition showed reductions in neuromuscular peripheral alterations only for KE (from –4.4 to –7.7%) and perceived muscle soreness scores (–8.3%). No significant differences in cardiorespiratory and RE responses as well as countermovement jump were identified between conditions in Post-1D. Discussion: Wearing high-pressure CGs (notably on KE) during DHR was associated with beneficial effects on soft-tissue vibrations, acute and delayed neuromuscular function and perceived muscle soreness. The use of CGs during DHR might contribute to the enhanced muscle recovery by exerting an exercise-induced “mechanical protective effect”.